Understanding the pregnant women's experiences during the COVID-19 pandemic in Macao: A qualitative study - Xin Wang; Ming Liu; Ka Ian Ho; Stephen Tee (Elsevier, 2022)
Objective: To explore and interpret the experiences of pregnant women in Macao during the COVID-19 pandemic. Methods: Recruitment advertisements were published through multiple social platforms in Macao. A purposive snowball sampling method was adopted to select interviewees. Eighteen women who were confirmed as pregnant from January to May 2020 participated in this qualitative study. Data was collected from November to December 2020 using in-depth personal interviews. One-to-one interviews were conducted by telephone to avoid personal contact. Thematic analysis was used to perform the data analysis and identify emergent themes. Results: Five themes emerged from the data analysis: changes in daily life, psychological distress, unique experiences of pregnancy follow-up, trying to pay attention to health information but also feeling overwhelmed, and change in hygiene behaviors due to fear of infection. Six sub-themes were identified: being confined at home but understanding the reasons, financial pressures and timely support from the government, perceived risk of catching the infection, retaining optimism with various help and support, adequate personal protections, and obsessive hygiene behaviors. Conclusion: During a pandemic, there is a risk of greater individual isolation, particularly for vulnerable groups such as women in pregnancy. The humanized attention to and support for the residents from the government buffered the adverse impact on the study participants. Preplanning for such events is needed to focus on psychological distress, financial constraints, and prenatal health services. Alternative service delivery, such as telemedicine, online counseling, and virtual reality (VR) technology, should be applied to offer pregnant women timely support and avoid a crisis.